Anterior shoulder instability - (:unkn) unknown (Springer Berlin Heidelberg, 2012)
Anterior shoulder instability; which is the most common type of all shoulder instabilities, needs to be evaluated carefully to achieve good prognosis. Every case should be evaluated by its own and proper treatment options should be planned according to this. Anatomy and biomechanics of the shoulder joint, especially the knowledge about the static and the dynamic factors are so important. In addition to the instability terminology; hyperlaxity which is a physiological condition should be mastered as well. For the proper treatment; correct diagnosis and the addressing of the involved pathology are two main points. Good history with proper physical examination and radiology are the crucial steps for the diagnosis. Acute anterior shoulder luxation with the first episode has totally a different treatment algorithm than recurrent anterior shoulder instability. The incidence of re-dislocation after the first episode is between 30% and 100%.; and the risk of re-dislocation will be higher if the first episode is at the age of 20 or below. The activity level is also important; especially patients with contact sports are in great risk. Generally our approach to acute anterior dislocation is conservative, but in recurrent anterior instability cases the aim of surgical treatment is to have anatomical reconstruction of the pathological lesion which is the fixation of capsulolabral tissue on the glenoid. Bony lesions, which might be the main reason of the failure should be evaluated carefully. © Springer-Verlag Berlin Heidelberg 2012.